Editorial (Italian Journal of Public Health, 2009)
It is rather difficult to give a unique definition of Health Services Research (HSR), since the concept of HSR has been evolving over the last 30 years. According to Last (1988), HSR can be considered the integration of epidemiologic, economic and other analytic sciences in the study of health services. HSR is a type of research, multidisciplinary in nature that can be conducted in several settings focusing on different purposes. The objective, according to the view of the Agency for Healthcare Research and Quality (2002), is to make research capable not only of identifying the most effective ways to organise, manage, finance and deliver high quality care, but also of reducing medical errors and improving patient safety. The relationship between HSR and public health is very strong: on one hand, both disciplines are concerned with the health status of the individual or of the population; while on the other hand, they deal with health systems, health intervention and factors that could influence health status.